2010
DOI: 10.1158/0008-5472.can-09-3929
|View full text |Cite
|
Sign up to set email alerts
|

A Large Prospective Study of Meat Consumption and Colorectal Cancer Risk: An Investigation of Potential Mechanisms Underlying this Association

Abstract: Although the relation between red and processed meat intake and colorectal cancer has been reported in several epidemiologic studies, very few investigated the potential mechanisms. This study examined multiple potential mechanisms in a large U.S. prospective cohort with a detailed questionnaire on meat type and meat cooking methods linked to databases for estimating intake of mutagens formed in meats cooked at high temperatures (heterocyclic amines, polycyclic aromatic hydrocarbons), heme iron, nitrate, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
363
4
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(391 citation statements)
references
References 36 publications
11
363
4
13
Order By: Relevance
“…Four large prospective studies found that a high intake of heme iron was associated with a higher risk of CRC (Lee et al, 2004;Larsson et al, 2005;Cross et al, 2010;Ferrucci et al, 2012) but no evidence for such an association was provided in two other studies (Kabat et al, 2007;Zhang et al, 2011). Estimation of heme iron from food intake is however difficult and subject to error as the proportion of heme iron in total Fe decreases with aging in beef (Ramos et al, 2012) and with heat treatment (Lombardi-Boccia et al, 2002;Purchas et al, 2004;D'evoli et al, 2009).…”
Section: Hemementioning
confidence: 99%
See 1 more Smart Citation
“…Four large prospective studies found that a high intake of heme iron was associated with a higher risk of CRC (Lee et al, 2004;Larsson et al, 2005;Cross et al, 2010;Ferrucci et al, 2012) but no evidence for such an association was provided in two other studies (Kabat et al, 2007;Zhang et al, 2011). Estimation of heme iron from food intake is however difficult and subject to error as the proportion of heme iron in total Fe decreases with aging in beef (Ramos et al, 2012) and with heat treatment (Lombardi-Boccia et al, 2002;Purchas et al, 2004;D'evoli et al, 2009).…”
Section: Hemementioning
confidence: 99%
“…For many years, diet is recognized as an important factor in disease etiology and risk of CRC (Modan, 1977), including the consumption of red and processed red meat. 1 Convincing epidemiological evidence linking red and processed red meat intake to CRC risk has accumulated over the last decades (Cross et al, 2010;Fung et al, 2010;Reedy et al, 2010;Chan et al, 2011;Shin et al, 2011;Ferrucci et al, 2012;Magalhaes et al, 2012;Johnson et al, 2013), and suggests that the CRC inducing effect is more pronounced for processed red meat compared to red meat. In parallel with these epidemiological observations, hypotheses on carcinogenic mechanisms underlying an association between CRC and the intake of red and processed red meat have been proposed and investigated in biological studies.…”
Section: Introductionmentioning
confidence: 99%
“…The perception of conventional red meat is relatively negative due to its high content in fat and saturated fatty acids, cholesterol, sodium and any other substances that may be involved in most prevalent diseases like cardiovascular diseases and diabetes (Micha et al 2010) and cancer (Cross et al 2010;Santarelli et al 2010). As an alternative to red meats, camel meat is considered a good source of high-quality protein with less fat, less cholesterol and a relatively higher amount of polyunsaturated fatty acids .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Most frequent mutations associated with CRC have been identified in adenomatous polyposis coli (APC), Kirsten-ras (KRAS) and TP53 genes. 3,4 The onset of colorectal cancer is special in the progression from normal epithelium to carcinoma involving sequential alterations in APC, KRAS and TP53.…”
mentioning
confidence: 99%